URGENSI PEMBENTUKAN REGULASI PENERIMABANTUAN IURAN BPJS KETENAGAKERJAAN BAGIPEKERJA RENTAN: PERSPEKTIF HUMAN RIGHTSBASED APPROACH - Raihan Bahrul Ilmi; Holyness N. Singadimedja (JOSH: Journal of Sharia, 2026)
The right to social security constitutes both a fundamental human right and a constitutional right guaranteed under Article 28H paragraph (3) and Article 34 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Although the National Social Security System has been implemented, Indonesia still lacks a specific regulatory framework concerning Contribution Assistance Recipients (Penerima Bantuan Iuran/PBI) within BPJS Ketenagakerjaan for vulnerable workers. This condition reveals a regulatory gap between the National Health Insurance Program, which already provides a government-funded contribution assistance scheme, and BPJS Ketenagakerjaan, which has not established a similar mechanism for vulnerable workers. This study aims to analyze the urgency of establishing regulations concerning Contribution Assistance Recipients within BPJS Ketenagakerjaan from a Human Rights-Based Approach (HRBA) perspective. The research employs a normative juridical method using statutory and conceptual approaches. The novelty of this study lies in its analysis of the legal vacuum regarding PBI BPJS Ketenagakerjaan through the HRBA framework, which positions vulnerable workers as rights holders and the state as the duty bearer responsible for ensuring the fulfillment of social security rights. The findings indicate that the absence of a PBI regulatory scheme within BPJS Ketenagakerjaan has resulted in the state's obligation to fulfill social security rights for vulnerable workers not being optimally implemented. The study further demonstrates that the vulnerable farmer protection program in Sijunjung Regency provides empirical evidence of the effectiveness of contribution assistance in expanding social security coverage. Therefore, the establishment of a Government Regulation concerning Contribution Assistance Recipients within BPJS Ketenagakerjaan is necessary to provide legal certainty, expand social security coverage, and strengthen social protection for vulnerable workers.